Consistency of "Probable RBD" Diagnosis with the RBD Screening Questionnaire: A Follow‐up Study. Issue 3 (1st November 2016) - Stefani, Ambra; Mahlknecht, Philipp; Seppi, Klaus; Nocker, Michael; Mair, Katherina J.; Hotter, Anna; Stockner, Heike; Willeit, Johann; Kiechl, Stefan; Rungger, Gregor; Gasperi, Arno; Poewe, Werner; et al.
Abstract: Introduction: The aim of this study was to evaluate the consistency of "probable RBD" diagnosis with the RBD screening questionnaire (RBDSQ) assessed 2 years apart in a population‐based study. Methods: Probable RBD was assessed by RBDSQ in 2008 and in 2010 in the Bruneck Study Cohort, with participants aged ≥60 years. Results: A total of 437 participants completed the RBDSQ in 2008 and 2010. There were 29 (6.6%) and 23 (5.3%) participants with probable RBD in 2008 and in 2010, respectively. Only eight (1.8%) screened positive on both occasions. RBDSQ values 2 years apart showed low correlation with each other (Spearman rank coefficient r = 0.348, P < 0.001) and low agreement (intraclass correlation coefficient 0.388, P < 0.001). Conclusions: We found low agreement between the two assessments. Possible explanations are the fluctuation of untreated RBD expression and the poor utility of the RBDSQ to detect RBD in the general population. Until further PSG validation of the RBDSQ in population‐based studies, investigators must be aware of the inherent uncertainty of questionnaire‐based RBD diagnosis.